PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, HARGA, PROMOSI DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA KONVEKSI CV. PESONA JEMBER ID - Dwi Saputra, Ananta; Fansuri Jusuf, Hamzah; Hidayah, Tamriatin (Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This study aims to determine the effect of product quality, service quality, price, promotion and location in a partial and simultaneous manner on purchasing decisions on CV Pesona Jember ID convection. The population in this study was consumers of CV Pesona Jember ID. The sample used was 60 respondents with roscoe formula. The sampling technique used is incidental sampling. The data analysis method uses multiple linear regression analysis with the help of SPSS 20. Tests used by instrument tests (validity tests and reliability tests), classical assumptions tests (normality tests, multicollinierity tests and heteroskedasticity tests), coefficient determination tests (R2) and hypothesis testing (test and test). The results of this study show that product quality, service quality, promotion and location have no partial effect on purchasing decisions and prices have a partial effect on purchasing decisions, then product quality, service quality, prices, promotions and locations have a simultaneous effect on purchasing decisions.